A systematic review on plant-based edible coatings for quality improvement and extended postharvest life of fresh fruits and vegetables - W. A. Harindra Champa; Aruna Weerasooriya (Journal of Horticulture and Postharvest Research)
Purpose: Use plant-based edible coatings (PBECs) for maintaining quality of fresh fruits and vegetables (FFVs) are trending upward. Compared to modified atmosphere packaging they eliminate the use of non-biodegradable polyethylene films. Therefore, the present study aimed to bring a comprehensive systematic review of the published literature on plant- based edible coatings (PBECs) for quality maintenance and extension of postharvest life FFVs. Findings: The results revealed that PBECs are a better alternative to other protective films and packaging materials that utilize non-biodegradable polyethylene films or inorganic chemicals which pose negative impact on both consumers and environment. A wide range of ingredients including biopolymers, leaf extracts, plant waxes, essential oils, and plant byproducts have been intensively researched for their potential applications in the development of edible coatings. The coating treatments significantly retarded the rates of respiration and ethylene emission, activated antioxidative defense mechanisms, suppressed cell wall degrading enzymes, and retarded colour deterioration; all of which led to protecting the biochemical and organoleptic properties of FFVs. Limitations: Food items, when coated with some of the edible coatings, alterations of flavour and degradation of their properties upon exposure to light, oxygen & high temperature have been noted. Further, poor stability of the developed emulsion resulting inconsistencies in their effectiveness have been reported. Conclusions: In conclusion, PBECs could be considered as promising eco and consumer friendly strategy for maintaining and extending the postharvest life of FFVs.  Future trends: It seems imperative to focus more on the development of composite coatings to enrich nutraceutical attributes of FFVs. Improving the efficacy of mode of action of the developed formulae alongside enhancing its stabilization and prevention of alterations in flavour when coated are critically important.